2017
DOI: 10.1371/journal.pone.0187928
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of anal human papillomavirus infection among HIV-negative men who have sex with men in Urumqi city of Xinjiang Uyghur Autonomous Region, China

Abstract: BackgroundInfection with human papillomavirus (HPV) is the most common sexually transmitted infection among men who have sex with men (MSM). Study on prevalence and risk factors of anal HPV infection among HIV-negative MSM in Northwestern China was rare.MethodsWe performed a cross-sectional study of HPV prevalence using anal swab specimens among HIV-negative MSM in Urumqi city of Xinjiang Uyghur Autonomous Region, China between April 1st and October 30th in 2016. Prevalence of any anal HPV infection, high-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…We identified 67 publications that were eligible for our anal ysis, 13-50,63-91 arising from 62 independent observational studies (119 248 participants). 33 17 reported STIs other than HIV as outcomes, 16,20,23,33,35,36,40,43,[46][47][48][49][50]65,68,70,74 and 12 reported both HIV infection and other STIs as outcomes. 17,25,27,32,34,39,41,[71][72][73]79,87,88,91 Four studies-two for HIV 15, 29 and two for other STIs 65,70were excluded from the meta-analysis because they did not report data necessary to calculate ORs (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 67 publications that were eligible for our anal ysis, 13-50,63-91 arising from 62 independent observational studies (119 248 participants). 33 17 reported STIs other than HIV as outcomes, 16,20,23,33,35,36,40,43,[46][47][48][49][50]65,68,70,74 and 12 reported both HIV infection and other STIs as outcomes. 17,25,27,32,34,39,41,[71][72][73]79,87,88,91 Four studies-two for HIV 15, 29 and two for other STIs 65,70were excluded from the meta-analysis because they did not report data necessary to calculate ORs (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Cumulative meta-analysis Men (n) Kreiss et al (1993) 73 Lafferty et al (1997) 74 Mor et al (2007) 79 Templeton et al (2009) 88 Jameson et al (2010) 71 Jozkowski et al (2010) 72 Zou et al (2010) 91 Goldstone et al (2011) 68 Mor et al (2012) 16 van Aar et al (2013) 27 van Aar et al (2013) 27 Pando et al (2013) 25 Canadas et al (2013) 20 Hu et al (2013) 23 Hu et al (2013) 23 Zeng et al (2014) 32 Zou et al (2014) 33 Liu et al (2015) 34 Okafor et al (2015) 35 Rebe et al (2015) 36 Qian et al (2016) 41 Crosby et al (2016) 39 Lee et al (2016) 40 Somia et al (2016) 43 Raghavendran et al (2017) 47 Qian et al (2017) 46 Tian et al (2017) 48 Xin et al (2017) 50 Wahome et al (2017) 49 Overall Heterogeneity I 2 =8% 496 744 20 832 1396 3828 24 900 390 589 448 310 453 482 450 204 446 520 163 690 423 200 1095 346 133 49 274 650 500 88 312 61 411…”
Section: Meta-analysismentioning
confidence: 99%
“…The mean age was 37 years ±3 years, similar between HIV-seropositive women (36.7 years) as compared to HIVseronegative women (37.3 years). The most represented age range was [30][31][32][33][34][35][36][37][38][39] years (44%). Single women were the most represented (58.88%), followed by married women (28.97%), widows (9.34%), and divorced (2.80%).…”
Section: Sociodemographic and Bioclinical Characteristics Of The Studmentioning
confidence: 99%
“…5 More particularly previous studies amongst sexually active MSM in China found that 33.8-62.8% had anal HPV. [6][7][8][9] In addition, the greater prevalence of HPV-related condyloma or as more commonly known genital warts, in MSM than for men who do not have sex with men often results to a greater physical and mental burden. 10 It has been identified that the high-risk HPV types 16 and 18 cause the majority of HPV-associated cancers whereas the low-risk HPV types 6 and 11 causes 90% of anogenital warts and the most cases of recurrent respiratory papillomatosis.…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been identified that the high-risk HPV types 16 and 18 cause the majority of HPV-associated cancers whereas the low-risk HPV types 6 and 11 causes 90% of anogenital warts and the most cases of recurrent respiratory papillomatosis. 6,11,12 The 2017 World Health Organization position paper on HPV vaccines recommended three HPV vaccines: 2v-HPV vaccine (Cervarix® prevents infection with HPV types 16 and 18), 4v-HPV vaccine (Gardasil® prevents infection with HPV types 6, 11, 16 and 18), 9v-HPV vaccine (Gardasil® 9 prevents infection with HPV types 6,11,16,18,31,33,45,52, and 58). 13 The efficacy of all three HPV vaccines has been verified by several clinical trials.…”
Section: Introductionmentioning
confidence: 99%